Islam and National Law: A Formal Legal Review on Sharia Laws in Aceh - Rani, Faisal A; Fikri, Fikri; Mahfud, Mahfud (Al-Risalah, 2020)
The implementation of sharia in Aceh has gone through a democratic process subscribed by the Unitary State of the Republic of Indonesia. Nevertheless, some observers consider it problematic. Against this backdrop, this article discusses the principles of the formalization of sharia into positive law and further concretely analyses the case of formalization of sharia in Aceh. Employing a normative approach on research of law, this article shows that the principles of sharia codified in the qanuns of Aceh are grounded on the QurÊ¾Än and the Sunna. The formalization of the sharia into the qanuns has gone through democracy and complies with the Indonesian law. Those qanuns contain regulations on Ê¿aqÄ«da, muÊ¿Ämala, Islamic convocation, and Islamic criminal law.